Immigration restriction, 'Americanization' and the Playground Movement. Issue 2 (15th March 2021) - Mobily, Kenneth E.
ABSTRACT: How did Joseph Lee hold to the contradictory ideas of immigration restriction and a willingness to use playgrounds as a means for assimilating immigrants into American cultural and civic traditions; how did he reconcile them in his own mind? The political climate and context of the Progressive Era are described to set the stage for the events Lee involved himself in – immigration restriction as a negative eugenic practice and 'Americanization' of immigrants as an expression of his upper class duty to the less fortunate. Lee's active role in the Immigration Restriction League and his unwavering commitment to the Playground Movement are reported in sharp contrast to one another. Finally, several explanations are offered for Lee's contradictory views on immigrants; the most likely explanation is that he saw both restriction and Americanization as two sides of the same 'coin' – what to do with people once they are born (and within America).